PESAN MULTIKULTURAL DALAM SERIAL FILM ANIMASI ANAK ADIT, SOPO, DAN JARWO: MULTICULTURAL MESSAGES IN THE ADIT, SOPO, AND JARWO CHILDREN'S ANIMATION FILM SERIES - Abdul Basid (Balai Penelitian dan Pengembangan Agama Jakarta, 2016)
This article is the result of a critical analysis of the animated series of Adit, Sopo, and Jarwo which showed on MNC TV and the series were uploaded on Youtube channel in June 2015. Through the content analysis method, this study concludes that the animated series of Adit, Sopo, and Jarwo bring the multicultural messages which shown from the different player characters through dialects, topics, and setting. For example, a dialect of Kang Ujang of the Sundanese background, the dangdut music as well as the view of Warung Tegal in the animated film. Taking the fact that there were messages of multiculturalism, the animated series, however, fails to feature more assorted diverse culture, culinary of the archipelago, the characters of other ethnic backgrounds as well as religious observances of Keywords: Multiculturalism, films analysis, children's movie series, animated films. Tulisan ini merupakan hasil dari analisa kritis terhadap tayangan serial animasi Adit, Sopo, dan Jarwo yang pernah ditayangkan di MNC TV dan telah diunggah di youtube, yang dilakukan pada bulan Juni 2015. Melalui analisis isi disimpulkan, bahwa serial animasi Adit, Sopo, dan Jarwo memuat pesan-pesan mutikulturalisme dari berbagai karakter pemain melalui dialek, topik, dan setting. Misalnya, dialek Kang Ujang yang kesunda-sundaan, dangdut, dan adanya Warung Tegal dalam film animasi tersebut. Walaupun telah ada pesan-pesan multikulturalisme, namun belum banyak menampilkan ragam budaya, kuliner nusantara, karakter etnik lainnya, dan peringatan keagamaan semua agama serta setting sosial masyarakat di luar kampung yang mencerminkan multikulturalisme bangsa. Kata Kunci: Multikultural, analislis film, film anak, film animasi.